THE IMPORTANCE OF ENZYME IMMUNOASSAY IN THE DIAGNOSIS OF INFECTIOUS DISEASES - Daminov Feruz Asadullayevich; Nabieva Farangiz Sadriddinovna; Abdusamadov Bobur Abdusamat O’g’li (Journal of new century innovations, 2023)
Annotation. At this time, there is a huge problem of quick and accurate diagnosis of some diseases that pose a threat to the life and health of the entire population. The rapid and uncontrolled spread of infectious diseases can lead to the development of an epidemic or even a pandemic. The most important component of the fight against infectious diseases is their timely laboratory diagnosis, which includes enzyme immunoassay. This article discusses the range of areas used and the principle of the enzyme immunoassay.